260 The National Center for Applied Reproduction and Genomics (NCARG) in Beef Cattle: Integrating Improvements in Reproductive and Genomic Technologies. (7th December 2018) - Patterson, D; Brown, D; Smith, M; Lamberson, W; Taylor, J; Spencer, T; Poock, S; Decker, J; Duff, G
Abstract: Recent and ongoing advances in reproductive and genomic research create opportunities for beef producers to make rapid gains in production efficiencies. However, economic impacts resulting from the adoption of these technologies have not been quantified to equip industry stakeholders with the financial rationale required to promote their adoption. Combining these technologies into production and marketing systems to maximize their economic impact on beef operations must be assessed to stimulate their wide-scale adoption. Currently, the U.S. is ill-equipped to transfer new and emerging technologies in reproduction and genomics to our nation's beef herds, as a limited number of land grant institutions employ specialists in disciplines related to reproduction and/or genetics and genomics. To combat this decline, a new approach focusing on a national center is needed. These considerations provided the rationale for a USDA-NIFA funded project with matching support from the University of Missouri to create a National Center for Applied Reproduction and Genomics (NCARG) in Beef Cattle. The Specific Aims of this project are to: 1) Quantify farm-level economic effects resulting from implementation of combinations of reproductive and genomic technologies; 2) Develop comprehensive curricula and training programs that will enable the various sectors of the beef industry to acquire new knowledge and skills; and 3) Implement comprehensive Extension programs that focus on the effective transfer of reproductive and genomic technologies to industry stakeholders. The overall goal and resulting outcomes from this project will definitively quantify farm-level economic effects resulting from implementation of reproductive and genomic technologies in U.S. beef herds; at the same time, the National Center for Applied Reproduction and Genomics will serve as our nation's training site to enable all segments of the beef cattle sector to acquire new knowledge and skills aiding in the successful adoption and long-term use of these technologies.